Digital Business Collaboration and Efficiency in Accounting Information System of Banyuwangi-Mall.Com - Setyowat, Yashinta; A. Gde Satia Utama, A. (International Journal of Engineering and Technology, 2018)
This study aims to produce information system designs related to e-commerce and add s-commerce functions and efficiency in providing integrated information or financial reports, in order to improve the efficiency of digital business in an accounting perspective. The method used is qualitative exploratory by using a case study approach to solve research problems. The data used in this study are primary and secondary data through interviews, observation, and documentation. The design of this collaboration system will provide convenience for users and also produce reports that are qualitative and can be used as a consideration in decision making. This research shows that between e-commerce and s-commerce can be collaborated and become a better system. Other studies emphasize only on one of them, between e-commerce and s-commerce, but in this study the two were collaborated to produce a new design. The results of this study can be used as study material for decision making to development e-commerce systems in banyuwangi-mall.com.